The Beauty of Melancholy and British Women Writers, 1670-1720 - Alexander, Laura (Cambridge Scholars Publisher, 2019)
This book considers melancholy language in representative works by several British women writers in late Stuart England. To understand how these women writers understood and reframed the discussion about melancholy and women's experience of suffering in their art, it turns to the twentieth-century French feminist theorist Julia Kristeva, whose radical work on melancholy in Black Sun: Depression and Melancholia (1989) provides an alternative psychoanalytic perspective for considering melancholy discourse created by women experiencing alienation, depression, and anguish in earlier periods. Kristeva offers a theoretical lens for understanding loss as a significant and ongoing perspective on life experience that finds expression through art and language. This text argues that early women writers created a new expressive mode, revising existing models to account for their own losses during a time of cultural and political transitioning in England. These writers provide a melancholy aesthetic in their works or depict depressed female figures reflecting artistic angst and a new discourse within language for articulating pain.
Description based on publisher supplied metadata and other sources
Keywords: Melancholy in literature; Electronic books